"I Had to Figure It Out": A Case Study of How Community College Student Parents of Color Navigate College and Careers. (April 2022) - Huerta, Adrian H.; Rios-Aguilar, Cecilia; Ramirez, Daisy
Objective: Community colleges, which can lead students to job opportunities and well-paying careers, are one of the main entry points to higher education for student parents. We use a conceptual framework that bridges career capital and community cultural wealth to understand student parents' college and career trajectories. This study asks (a) How do student parents of color navigate community college? (b) How do student parents of color make educational and career decisions?, and (c) What, if any, institutional resources do student parents of color utilize to learn about career planning and workforce transition resources at their campus?Method: This qualitative case study draws from individual and focus group interviews with 67 student parents of color to better understand how they tap into their cultural knowledge and lived experiences to navigate college and make career decisions.Results: Data speaks to (a) student parents' difficulty maneuvering life as a college student and parent; and (b) the importance of students' familial and institutional support networks as they seek college and career information.Contributions: We hope these findings will encourage community colleges to (re)consider their current practices relating to the student parent population which includes identifying and tracking student parents, implementing guided pathways with their unique needs in mind, communicating services offered to student parents, and creating a more welcoming environment for students and their families.